The I-OPTA Questionnaire: A National Assessment of Patients with Neovascular Age-Related Macular Degeneration - Benjamin Sommer Thinggaard; Kasper Hansen; Freja Dinesen; Maria Kjøller Pedersen; Lars Morsø; Yousif Subhi; Jakob Grauslund; Lonny Stokholm (Ophthalmology and Therapy)
Abstract Introduction Neovascular age-related macular degeneration (nAMD) is the leading cause of irreversible vision loss in developed countries. However, a significant gap persists in understanding this population, exacerbated by their advanced age and visual impairments, which can hinder research participation and access to healthcare. The purpose of this study was to describe the content of the questionnaire and the participating patients with nAMD. Methods The survey includes patients diagnosed with nAMD who had previously received treatment or were currently undergoing intravitreal anti-vascular endothelial growth factor (anti-VEGF) injections. Participants were recruited using various methods, as reaching out to patients who are no longer receiving treatment poses a particular challenge. A patient and public advisory board assisted throughout the study period. Results Of the 713 electronic invitations sent out, 494 (69.3%) patients responded to the questionnaire, with an additional 57 responses obtained through e-mail or telephone interviews. Due to the exclusion of 16 responses, there were a total of 535 valid responses, including 176 from patients previously treated and 359 from those currently undergoing treatment for nAMD. The median age of respondents was 79.9 years (interquartile range [IQR] 75.5–84.7), with 59.8% being women. Among them, 53.2% were married, while 43.1% lived alone. Conclusions Data from the I-OPTA (Identification of Patient-Reported Barriers in Treatment for nAMD) questionnaire allows future exploration of patients who are no longer receiving treatment, patients’ knowledge about preventive measures, and the impact of nAMD on visual function and quality of life. Future research, including studies that integrate data from corresponding retinal images and Danish national registers, has the potential to generate invaluable knowledge, providing benefits to both patients and healthcare professionals.